2019
DOI: 10.1038/s41429-019-0240-6
|View full text |Cite
|
Sign up to set email alerts
|

Trimethoprim and other nonclassical antifolates an excellent template for searching modifications of dihydrofolate reductase enzyme inhibitors

Abstract: The development of new mechanisms of resistance among pathogens, the occurrence and transmission of genes responsible for antibiotic insensitivity, as well as cancer diseases have been a serious clinical problem around the world for over 50 years. Therefore, intense searching of new leading structures and active substances, which may be used as new drugs, especially against strain resistant to all available therapeutics, is very important. Dihydrofolate reductase (DHFR) has attracted a lot of attention as a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
73
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 185 publications
0
73
0
2
Order By: Relevance
“…TMP is a pyrimidine antifolate drug, which exerts antimicrobial activity by blocking the reduction of dihydrofolate to tetrahydrofolate, the active form of folic acid, by susceptible organisms [ 2 , 24 , 25 ]. One of our reviews presents an extensive range of research literature on the first and most recent achievements in TMP analogs as DHFR inhibitors and underlines new directions in developing and modeling DHFR inhibitors [ 26 ]. This literature analysis confirms that there are only a few reports showing the anticancer activity of TMP analogs.…”
Section: Introductionmentioning
confidence: 99%
“…TMP is a pyrimidine antifolate drug, which exerts antimicrobial activity by blocking the reduction of dihydrofolate to tetrahydrofolate, the active form of folic acid, by susceptible organisms [ 2 , 24 , 25 ]. One of our reviews presents an extensive range of research literature on the first and most recent achievements in TMP analogs as DHFR inhibitors and underlines new directions in developing and modeling DHFR inhibitors [ 26 ]. This literature analysis confirms that there are only a few reports showing the anticancer activity of TMP analogs.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of this inhibition consists in preventing the conversion of DHF to an active form, i.e., THF [3,32]. One of our reviews presents an extensive range of research literature on the first and most recent achievements in TMP analogs as DHFR inhibitors and underlines new directions in developing and modeling DHFR inhibitors [33]. Currently, Pedrola et al [34] showed group of TMP analogs display meaningful structural features of the initial drug together with relevant modifications at several points, keeping antibiotic potency and showing satisfactory antimicrobial profile (good activity levels and reduced growth rates), especially against methicillin-resistant Staphylococcus aureus (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Compounds containing pyrimidine, pteridine and azine moieties have already been reported as good DHFR inhibitors. 33,34 The rate of folate metabolism accelerates during microbial infection owing to their particular DNA and for protein synthesis to maintain proper cell replication. Taking advantage of this accelerated rate of metabolism, folic acid antagonists have been used to treat various microbial infections.…”
Section: Introductionmentioning
confidence: 99%